1994
DOI: 10.1159/000106694
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Dementia, Neuropsychological and MRI Findings in Multiple Sclerosis

Abstract: Twenty patients diagnosed as having multiple sclerosis (MS) were examined by MRI and 9 neuropsychological scales: MMSE, BCRS, RMB, SDMT, BNT, VM, FAS, Benton and Hamilton. The number and distribution of the lesions, and cerebral and corpus callosum atrophy were evaluated by MRI. MR images were generated by a 0.5 Tesla instrument utilizing T1WI, PD and T2WI imaging techniques. The results reveal (1) that patients with MS are impaired in a broad range of cognitive functions but mainly memory is affected; (2) num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
0
17
0
4
Order By: Relevance
“…Cerebral white matter (WM) has been a target for investigation, given the propensity of MS to affect WM. Studies performing quantification and mapping of macroscopic WM lesions have identified associations between lesion distribution and disability [3][4][5][6][7][8] , but fail to take into account widespread diffuse damage present in normal-appearing WM (NAWM). A technique which is sensitive to this damage 9,10 , diffusion tensor imaging (DTI), allows quantification of fractional anisotropy (FA), a marker of ultrastructural WM integrity that has been used for more than a decade to study both lesional and NAWM damage in MS [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral white matter (WM) has been a target for investigation, given the propensity of MS to affect WM. Studies performing quantification and mapping of macroscopic WM lesions have identified associations between lesion distribution and disability [3][4][5][6][7][8] , but fail to take into account widespread diffuse damage present in normal-appearing WM (NAWM). A technique which is sensitive to this damage 9,10 , diffusion tensor imaging (DTI), allows quantification of fractional anisotropy (FA), a marker of ultrastructural WM integrity that has been used for more than a decade to study both lesional and NAWM damage in MS [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Selective atrophy of the hippocampus has been described in relapsing-remitting multiple sclerosis (RRMS) [11], and this has been found to correlate with performance in tests of verbal learning/recall in MS patients [11], [12]. Atrophy of the thalamus occurs in MS [13], [14], and shows a significant relationship to cognitive performance when measured directly or indirectly [15], [16], [17], [18]. Mammillary body atrophy has also been identified in MS [19], but the cognitive relevance of this finding has not, to our knowledge, been tested.…”
Section: Introductionmentioning
confidence: 99%
“…However, several potentially important aspects of the hand function remained unexplored. For example, the corpus callosum plays a major role in interhemispheric transfer and integration of sensorimotor information in bimanual movements (Seymour, Reuter-Lorenz, & Gazzaniga, 1994), and it appears to be affected frequently even in mildly involved MS patients (Mendez, 1995;Tsolaki et al, 1994). Therefore, it remains possible that the MS patients could reveal a noticeable deterioration in bimanual manipulation tasks.…”
mentioning
confidence: 99%